Manuscript 50 of the Alessandrina University Library: user manual for the Libraria of Francesco Maria II della Rovere - Daniela Fugaro (Bibliothecae.it)
Of the Libraia impressa that Francesco Maria II della Rovere collected and organised between the end of the 16th century and the first thirty years of the 17th century in Casteldurante - a Bibliotheca universalis of imperishable fame, transferred in 1667 at the behest of Pope Alexander VII to the newly established Biblioteca Alessandrina - a manuscript inventory still exists. It is a unique document (today B.U.A., Ms. 50) also in terms of complexity and care in its editing, divided into three parts: a systematic topographical catalogue, a catalogue by authors and works - in which the authors are listed in alphabetical order under their proper names - and a list of headwords from the surname to the name of the authors themselves. Starting with an analysis of the organisation of the sub-scansia De architectura militari (part of Scansia 42 De re militari, Architectura et Mechanicis) and comparing it with the copies that belonged to the duke that are now in the Biblioteca Alessandrina, Daniela Fugaro tackled some of the library-economic problems related to the constitution and management of the Durantine collection not only in the specific context of the Duchy of Urbino, but also after its devolution to the Holy See. The choice of the topic of fortifications and military architecture was dictated by the consideration that Federico da Montefeltro, Francesco Maria I and Francesco Maria II considered the art of war an essential tool for asserting their autonomy vis-à-vis the Papacy, to which, however, they were closely linked. The virtuous practice of arms also remained for the last della Rovere family a conditio sine qua non of good governance. To achieve satisfactory results, Francis Mary II took as his models both Francis Mary I, the valiant soldier and founder of the dynasty, and Federico da Montefeltro, the condottiere who had brought the Duchy of Urbino to its first splendour.